Christology from below : an examination of the black christology of Takatso Mofokeng in the context of the development of black theology in South Africa and in critical relation to the christological ethic of Dietrich Bonhoeffer - Forrest, Martin R (Department of Religious Studies, 2015)
Bibliography: leaves 188-197.